A cost analysis approach to valuing cover crop environmental and nitrogen cycling benefits: A central Illinois on farm case study. (January 2018) - Roth, Richard T.; Ruffatti, Michael D.; O'Rourke, Patrick D.; Armstrong, Shalamar D.
Abstract: The use of cover crops (CC) in row crop agricultural systems has been shown to provide numerous environmental benefits along with increasing overall soil health. The environmental benefits of CC are well known and demonstrated in the literature. However, before voluntary widespread CC adoption can occur, methods for potential CC cost recovery must be explored. Therefore, the objectives of this study were to quantify the environmental and nitrogen (N) cycling benefits observed from CC and to determine the potential of those benefits to offset the costs of CC implementation. This experiment used data collected between CC planting in 2014 and cash crop harvest in 2016 from an associated study conducted at the Illinois State University Nitrogen Management Research Field Station, in Lexington, IL. In this case study, CC were integrated into two cropping systems common to Central IL, split application of N with the dominant portion of N applied in the spring (20%fall, 80% spring) with and without CC, and a split N application with the dominant portion of N applied in the fall (70% fall, 30%spring) with and without CC. The chosen CC for the study was a 92% cereal rye ( Secale cereal L. ) and 8% daikon radish ( Raphanus sativus L. ) blend, and data were collected for both strip-till corn ( Zea mays L. ) and no-till soybeans ( Glycine max L. ). Different from existing attempts to model the economic value of CC, this model includes input variables that quantify the reduction of N loss through tile drainage, the return of N from CC residue following termination and reductions in soil erosion. We determined that valuing the impact of CC on subsurface drainage N loading, soil erosion, and CC residue N mineralization has the potential to recover an average of 61% of the costs associated with CC implementation. More specifically, the average composition of recovered costs was 34% from reductions in N loading to subsurface drainage, 57% from the tile-adjusted mineralization of N from the CC biomass, and 9% from the estimated reduction in erosion. The results of this study have the potential to provide a more comprehensive assessment of CC value that could help producers make informed N and CC management decisions. Highlights: Valuation of cover crop environmental and N cycling benefits. Average cost recovery from environmental and N cycling cover crop benefits was 61%. Cover crop cost recovery was maximized with equal cash crop yields.